The Role of Psychological Adaptation in Facing Climate Change Impacts - Rusmayadi, Gusti; Salawati, Umi; Priyana, Yana (West Science Interdisciplinary Studies, 2024)
Climate change presents a multifaceted challenge requiring not only physical adaptation but also psychological resilience from individuals and communities. Despite its significance, the literature on psychological adaptation to climate change remains fragmented. This study conducts a comprehensive bibliometric analysis to systematically examine the existing research on psychological adaptation to climate change, aiming to identify key themes, gaps, and trends. The analysis reveals a growing interest in understanding the psychological dimensions of climate change adaptation, with research spanning topics such as mental health impacts, social adaptation strategies, and ecological responses. Key thematic clusters identified underscore the interdisciplinary nature of climate change research, highlighting the need for collaborative efforts to address this complex issue effectively. The findings provide valuable insights for advancing our understanding of psychological adaptation to climate change and informing the development of evidence-based adaptation strategies.